Optimization of Warehouse Management in Company A - Cao, Zhengyan; Jiang, Xiuhua (International Journal of Global Economics and Management, 2024)
China’s modernization of warehouse management started late, advanced technology management level, management experience is more lacking, and the advanced warehouse management level of developed countries there is still a certain gap. This paper takes Company A as an example to conduct in-depth research and analysis and summarization. lt is found that the main problems in the process of warehouse management are concentrated in the complexity of the warehouse operation process, unreasonable warehouse planning, lack of inventory control, low warehouse picking efficiency, warehouse picking efficiency is low and other five aspects, according to the problems that exist in the warehouse space management, warehouse picking workflow optimization, reduce warehouse management costs, improve warehouse picking efficiency and other improvements to countermeasures in order to enhance the company’s warehousing management capabilities and level.